Approach to the international scene of automatic promotion and school retention at the basic educational level. A systematic review (Innovaciones Educativas, 2021)
The objective of the study is to present a systematic review between the years 2010-2020 about studies that have addressed automatic promotion and school retention in basic education. For this, three dimensions. are considered: academic, emotional and social of preschool, primary and secondary students, through research results generated at an international level. Standards proposed by the PRISMA declaration were used and the selection criteria of the documents were established based on the PEO strategy. Among the main databases used are ERIC, EBSCO and Google Scholar. The results highlight the documentary production over the empirical. Likewise, it was found that the practices of automatic promotion and school retention have been studied largely through the school achievements of students. The main findings highlight in the emotional dimension an improvement in self-esteem and greater personal security in the students. On the social side, the permanence of the most vulnerable students in the educational system is ensured. And academically, automatic promotion is distinguished as the cause of the poor educational level of students. Primary level studies predominate. It is concluded that automatic promotion and school retention are not effective strategies. For some it could be beneficial, but for others, both automatic promotion and retention can trigger academic deficiencies or low self-esteem in students. Actors in the educational field promote the establishment of alternative strategies to automatic promotion and retention.
Keywords: automatic promotion; retention; formal education; educational inspection; school performance; learning process